Kajian Yuridis Tindak Pidana Gratifikasi Oleh Pejabat Negara - Bustomi Bustomi (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Corruption is a special criminal act that is regulated outside the Criminal Code (KUHP). Especially because this issue is regulated separately outside the Criminal Code (Criminal Code). Because in accordance with Article 103 of the Criminal Code, it is emphasized that: